The Kiai’s Efforts In Developing Multicultural Education In Pesantren Langitan Widang Tuban - Victor Imaduddin Ahmad; Sudarto Murtaufiq (Akademika, 2020)
The presence of Muslim clerics (kiai) in Langitan Islamic boarding school (pesantren) Widang Tuban is very unique to be taken into account, especially from their duties and function. They have provided direction or input in curriculum preparation, created an evaluation system, formulated institutional rules and organized the life of the entire pesantren community as well as their role as community leaders. This study focuses more on the efforts of kiai in developing multicultural Islamic education for considering that this pesantren has undergone changes and renewal but is not inseparable from traditional roots which are proven to be laden with multicultural educational values. In reality, this kind of pesantren has produced many students and graduates who have inclusive, moderate and tolerant viewpoints. This study uses a descriptive qualitative approach. Data collection is caccried out through such methods as observation, interviewes and documents. The results of this study showed that the efforts of the kiai in developing multicultural Islamic education in Pesantren LangitanWidang Tuban are: firstly, building a multicultural Islamic education epistemology based on the al-Qur'an and Hadith. Secondly, sharpening the values of multiculturalism in curriculum. Thirdly, fostering students' spiritual growth (spiritualization of students).